INTERAÇÃO NÍQUEL E NITROGÊNIO EM PLANTAS DE MILHO - Marcia Leticia Monteiro Gomes (2023)
Nickel (Ni) is considered a micronutrient and has a narrow range between the amount to meet the nutritional requirement of the plant and that which may cause toxicity. The handling of Ni fertilization needs to be adequate, as the excess of this micronutrient can cause symptoms of toxicity, impairing the development of the plant. This study aimed to evaluate the effect of foliar application of Ni doses on maize plants, to verify whether the applied Ni promotes gains in gas exchange and grain yield, due to the improvement in plant nutrition, biochemistry and physiology. The design used was in randomized blocks (DBC) with 5 doses of Ni: 0; 20; 40; 80 and 160 g ha-1 of Ni via foliar application (divided into two applications), with 4 replications, totaling 20 plots. Analyzes of photosynthetic pigments and gas exchange were performed. The physiological variables evaluated were: photosynthesis, internal CO2 concentration, stomatal conductance, instantaneous efficiency in water use, and instantaneous efficiency in carboxylation. In addition to the analysis of Ni content in the leaf and grain and grain yield. All evaluations were carried out at the same VT phenological stage (pinning), on the first completely developed leaf with a visible sheath. By means of regression analysis, the data were adjusted to the quadratic and linear model with the increment of Ni doses. In view of this, foliar application of Ni is an alternative for maize nutrition. The dose of 80 g ha-1 of Ni was the one that most contributed to the development of the corn crop, since the application of Ni via the leaves favored the levels of total chlorophyll, carotenoids, photosynthesis, instantaneous efficiency in water use, and instantaneous efficiency in carboxylation. Ni contents differed in plant parts and were higher in leaves. The dose of 160 g ha-1 of Ni caused a decline in the physiological variables, photosynthetic pigments, A, ICE, WUE and increased Ci contents. Corn yield did not increase in response to Ni foliar application.